Hydrolysis of sorghum starch for ethanol production - Nadir, Najiah; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Mohd Yunus, Rosli (2010)
The conversion of starch to sugar can be achieved by hydrolysis process. The two-step enzymatic hydrolysis of sweet sorghum was performed by commercially available α- amylase and glucoamylase. In order to attain a higher sugar yield, a study was carried out to investigate the effect of main factors of the hydrolysis process, namely, amount of substrate, liquefaction and saccharification temperature, liquefaction and saccharification time, and amount of α-amylase and glucoamylase enzymes. As shown in the analysis of variance (ANOVA) result, the amount of substrate, liquefaction and saccharification temperature, and amount of glucoamylase enzyme have contributed more significant effect on hydrolysis process of sweet sorghum for sugar production. Also, glucose was found to be the main product obtained from the hydrolysis of sweet sorghum starch.